Evolution of Wearable Devices in Health Coaching: Challenges and Opportunities - Tahri Sqalli, Mohammed; Al-Thani, Dena (Frontiers in Digital Health, 2020)
Wearable devices hold an enormous potential in contributing to an improved global health. The availability, non-invasiveness and affordability of those systems make them promising candidates to transform the standard of care for health coaching. These wearable devices are now considered as versatile coaching systems for patients who wish to improve their health and well-being. The timeliness of the "wearable device as a health coaching enabler" field of research will inevitably know a prominent growth in the upcoming years from both the computing and the medical perspective. In this perspective article, we list the potential challenges as well as the opportunities of this newly-born field from an interdisciplinary perspective, mainly focusing on both the computing and healthcare. We also chart guidelines for the healthcare research community who is willing to get involved in the computing field to harness the benefits of wearable devices.